STAR/STARD1: A mitochondrial intermembrane space cholesterol shuttle degraded through mitophagy - Prasanthi P. Koganti; Amy H. Zhao; Michael C. Kern; Auriole C. R. Fassinou; Vimal Selvaraj (Proceedings of the National Academy of Sciences, 2025)
The import of cholesterol to the inner mitochondrial membrane by the steroidogenic acute regulatory protein (STAR/STARD1) is essential for de novo steroid hormone biosynthesis and the alternate pathway of bile acid synthesis. This robust system, evolved to start and stop colossal cholesterol movement, ensures pulsatile yet rapid mitochondrial steroid metabolism in cells. Nonetheless, the proposed mechanism and components involved in this process have remained a topic of ongoing debate. In this study, we elucidate the mitochondrial import machinery and structural aspects of STAR, revealing its role as an intermembrane space cholesterol shuttle that subsequently undergoes rapid degradation by mitophagy. This mechanism illuminates a fundamental process in cell biology and provides precise interpretations for the full range of human STAR mutation-driven lipoid congenital adrenal hyperplasia in patients.